Single event visualization of unconventional secretion of FGF2 - Dimou, Eleni; Katsinelos, Taxiarchis; Wegehingel, Sabine; Nickel, Walter (The journal of cell biology, 2019)
FGF2 is exported from cells by an unconventional secretory mechanism. Here, we directly visualized individual FGF2 membrane translocation events at the plasma membrane using live cell TIRF microscopy. This process was dependent on both PI(4,5)P2-mediated recruitment of FGF2 at the inner leaflet and heparan sulfates capturing FGF2 at the outer plasma membrane leaflet. By simultaneous imaging of both FGF2 membrane recruitment and the appearance of FGF2 at the cell surface, we revealed the kinetics of FGF2 membrane translocation in living cells with an average duration of ∼200 ms. Furthermore, we directly demonstrated FGF2 oligomers at the inner leaflet of living cells with a FGF2 dimer being the most prominent species. We propose this dimer to represent a key intermediate in the formation of higher FGF2 oligomers that form membrane pores and put forward a kinetic model explaining the mechanism by which membrane-inserted FGF2 oligomers serve as dynamic translocation intermediates during unconventional secretion of FGF2.
Published online: 23 November, 2018
Gesehen am 30.10.2019